Epigraphs in Mutis novels - Castro García, Óscar (Íkala, Revista de Lenguaje y Cultura, 1999)
Epigraphs are one of the paratextual elements, which refer us back to the idea of model author. These elements enhance a reading which interweaves the text of a literary work to other cultural texts. In Alvaro Mutis'work, characterized by an astounding thematical richness and the use of a variety of languages, the epigraphs gain new privileges. Since his early production, this Colombian writer disseminated them throughout his poetry and his novels, engraving them with his aesthetical and ethical obsessions.